Catastrophic health expenditures, insurance churn, and nonemployment among gynecologic cancer patients in the United States - Albright, Benjamin B.; Nitecki, Roni; Chino, Fumiko; Chino, Junzo P.; Havrilesky, Laura J.; Aviki, Emeline M.; Moss, Haley A. (American journal of obstetrics and gynecology, 2022)
In recent years, there has been growing recognition of the financial burden of severe illness, including associations with higher rates of nonemployment, uninsurance, and catastrophic out-of-pocket health spending. Patients with gynecologic cancer often require expensive and prolonged treatments, potentially disrupting employment and insurance coverage access, and putting patients and their families at risk for catastrophic health expenditures. This study aimed to describe the prevalence of insurance churn, nonemployment, and catastrophic health expenditures among nonelderly patients with gynecologic cancer in the United States, to compare within subgroups and to other populations and assess for changes associated with the Affordable Care Act. We identified respondents aged 18 to 64 years from the Medical Expenditure Panel Survey, 2006 to 2017, who reported care related to gynecologic cancer in a given year, and a propensity-matched cohort of patients without cancer and patients with cancers of other sites, as comparison groups. We applied survey weights to extrapolate to the US population, and we described patterns of insurance churn (any uninsurance or insurance loss or change), catastrophic health expenditures (>10% annual family income), and nonemployment. Characteristics and outcomes between groups were compared with the adjusted Wald test. We identified 683 respondents reporting care related to a gynecologic cancer diagnosis from 2006 to 2017, representing an estimated annual population of 532,400 patients (95% confidence interval, 462,000–502,700). More than 64% of patients reported at least 1 of 3 primary negative outcomes of any uninsurance, part-year nonemployment, and catastrophic health expenditures, with 22.4% reporting at least 2 of 3 outcomes. Catastrophic health spending was uncommon without nonemployment or uninsurance reported during that year (1.2% of the population). Compared with patients with other cancers, patients with gynecologic cancer were younger and more likely with low education and low family income (≤250% federal poverty level). They reported higher annual risks of insurance loss (8.8% vs 4.8%; P=.03), any uninsurance (22.6% vs 14.0%; P=.002), and part-year nonemployment (55.3% vs 44.6%; P=.005) but similar risks of catastrophic spending (12.6% vs 12.2%; P=.84). Patients with gynecologic cancer from low-income families faced a higher risk of catastrophic expenditures than those of higher icomes (24.4% vs 2.9%; P<.001). Among the patients from low-income families, Medicaid coverage was associated with a lower risk of catastrophic spending than private insurance. After the Affordable Care Act implementation, we observed reductions in the risk of uninsurance, but there was no significant change in the risk of catastrophic spending among patients with gynecologic cancer. Patients with gynecologic cancer faced high risks of uninsurance, nonemployment, and catastrophic health expenditures, particularly among patients from low-income families. Catastrophic spending was uncommon in the absence of either nonemployment or uninsurance in a given year.